Criscianthus, a new genus of Eupatorieae (Asteraceae) with a key to members of the tribe in Africa - Grossi, Mariana Andrea (2013)
Stomatanthes zambiensis is segregated from the African genus Stomatanthes and raised as the only species of the new genus Criscianthus (Eupatorieae, Asteraceae). Criscianthus zambiensis is characterized by its verticillate phyllotaxy with three leaves per node, phyllaries with caudate apex, and an exclusive type of hair in its cypsela. A full description of the genus and its species, a morphological analysis, photographs, illustrations, and a distribution map are provided. A key to native and alien species of the tribe Eupatorieae in Africa is included.